On Four-Dimensional Paracomplex Structures with Norden Metrics - İşcan, M. and Özkan, M. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study almost paracomplex structures with Norden metric on Walker 4-manifolds and try to find general solutions for the integrability of these structures on suitable local coordinates. We also discuss para-Kähler (paraholomorphic) conditions for these structures.